CHARACTERIZATION OF IMMOBILIZED LIPASE IN ALUMINOSILICATE FOR LACTOSYL PALMITATE SYNTHESIS - Anna Roosdiana; Tutik Setianingsih; Diah Mardiana; Suratmo Suratmo (Universitas Gadjah Mada, 2009)
Whey lactose can be esterified enzymatically by using immobilized lipase. The lipase can be isolated from Rhizopus oryzae, purified and immobilized in mesoporous aluminosilica. The use of immobilized lipase has advantages, there are longer shelf life and repeatable use. It is necessary to characterize the immobilized lipase dan ester product. The aim of the research was to characterize immobilized lipase, including determination lipase adsorption type in mesoporous aluminosilicate, immobilized lipase stability during storage time, efficiency of repetitive use of immobilized lipase. The result showed that lipase adsorption in mesoporous aluminosilicate was physical adsorption type through hydrogen bound and electrostatic interaction. Immobilized lipase stability was relatively constant at storage temperature 5 °C for 25 days resulting in 98.16% of initial activity. The repetitive use of immobilized lipase showed efficient until 5 uses within activity of 50.22%. The IR spectra of lactosyl palmitate from both whey and pure lactose result showed bands at wavelength number of 3462 cm-1(OH bond), 1739 cm-1 and 1747 (C=O ester bond) 1295 cm-1 dan 1242 cm-1 (C-O ester bond). In addition, the HLB value for lactosyl palmitate (whey) 4.708 and lactosyl palmitate (pure lactose) 4.715, therefore both lactosyl palmitate is appropriate as emulgator in W/O.